Dynamics of zinc (Zn) and nickel (Ni) in a cerrado oxisol treated with sewage sludge for a long period - de Macedo, Fernando Giovannetti; de Melo, Wanderley José [UNESP]; Merlino, Luciana Cristina Souza [UNESP]; Donha, Riviane Maria de Albuquerque [UNESP]; de Melo, Gabriel Maurício Peruca [UNESP]; Junior, José Lavres (My University, 2014)
Sewage sludge can be a source of micronutrients, such as zinc (Zn) and nickel (Ni), for Cerrado soils; however, since they are heavy metals, continuous use of this residue requires an evaluation of the dynamics of these elements in the soil/plant system. This study aimed to evaluate the dynamics of Zn and Ni in a soil/plant system regarding extraction methods to determine the quantity of plant nutrients in the soil as well as the soil enzymatic activity in an area treated with sewage sludge for eleven years. Sewage sludge was applied annually in an Oxisol and a crop was sown. The accumulated sewage sludge doses throughout the eleven years of the experiment were 0 as control, 55, 110 and 167.5 Mg ha-1, and corn was the test crop. At 60 days after sowing, corn soil samples were collected from the 0-10 cm layer (for analysis of enzymatic activity) and 0-20cm, 20-40 cm (for analysis of Zn and Ni). The activities of the enzymes urease and dehydrogenase and the extractors Mehlich-1, Mehlich-3 and DTPA were evaluated. The increments of Zn and Ni in the Cerrado Oxisol as a function of sewage sludge application over a long time were small. The Mehlich-3 extractant was the best correlated with Zn and Ni extraction by the corn plants. In the eleventh year of application, sewage sludge was not efficient at supplying Zn to plants. The application of high doses of sewage sludge for a long time affects soil enzymatic activity.
Keywords: Biosolids; Environmental pollution; Extractors; Heavy metals; Plant nutrition